The problem of monitoring the formation future teachers’ political culture - Gritsay, S. M. (Problems of Engineer-Pedagogical Education, 2018)
This article deals with the problem of monitoring the formation future teachers’ political culture. The essence and structure (goal-oriented, motivating, cognitive, activity-oriented, reflexive, personality-oriented)of prospective teacher’s political culture are defined. Only socially mature teacher can manage these tasks having his own formed political culture. The essence of the monitoring process specified on the synchronization monitoring, receiving the knowledge about the state of the object and modeling, forecasting and decision management solution that makes it possible to receive prompt information about course teaching process, its effectiveness, draw conclusions about positive and negative sides, timely adjust it. The functions of monitoring the formation of future teachers’ political culture were describe. The criteria (motivational and value, content and procedural, personal and reflective) and the rates of formation political culture future teachers hadbeen identified.